Detecting and confirming residual hotspots of lymphatic filariasis transmission in American Samoa 8 years after stopping mass drug administration. - Colleen L Lau; Sarah Sheridan; Stephanie Ryan; Maureen Roineau; Athena Andreosso; Saipale Fuimaono; Joseph Tufa; Patricia M Graves (PLoS Neglected Tropical Diseases, 2017)
The Global Programme to Eliminate Lymphatic Filariasis (LF) aims to eliminate the disease as a public health problem by 2020 by conducting mass drug administration (MDA) and controlling morbidity. Once elimination targets have been reached, surveillance is critical for ensuring that programmatic gains are sustained, and challenges include timely identification of residual areas of transmission. WHO guidelines encourage cost-efficient surveillance, such as integration with other population-based surveys. In American Samoa, where LF is caused by Wuchereria bancrofti, and Aedes polynesiensis is the main vector, the LF elimination program has made significant progress. Seven rounds of MDA (albendazole and diethycarbamazine) were completed from 2000 to 2006, and Transmission Assessment Surveys were passed in 2010/2011 and 2015. However, a seroprevalence study using an adult serum bank collected in 2010 detected two potential residual foci of transmission, with Og4C3 antigen (Ag) prevalence of 30.8% and 15.6%. We conducted a follow up study in 2014 to verify if transmission was truly occurring by comparing seroprevalence between residents of suspected hotspots and residents of other villages. In adults from non-hotspot villages (N = 602), seroprevalence of Ag (ICT or Og4C3), Bm14 antibody (Ab) and Wb123 Ab were 1.2% (95% CI 0.6-2.6%), 9.6% (95% CI 7.5%-12.3%), and 10.5% (95% CI 7.6-14.3%), respectively. Comparatively, adult residents of Fagali'i (N = 38) had significantly higher seroprevalence of Ag (26.9%, 95% CI 17.3-39.4%), Bm14 Ab (43.4%, 95% CI 32.4-55.0%), and Wb123 Ab 55.2% (95% CI 39.6-69.8%). Adult residents of Ili'ili/Vaitogi/Futiga (N = 113) also had higher prevalence of Ag and Ab, but differences were not statistically significant. The presence of transmission was demonstrated by 1.1% Ag prevalence (95% CI 0.2% to 3.1%) in 283 children aged 7-13 years who lived in one of the suspected hotspots; and microfilaraemia in four individuals, all of whom lived in the suspected hotspots, including a 9 year old child. Our results provide field evidence that integrating LF surveillance with other surveys is effective and feasible for identifying potential hotspots, and conducting surveillance at worksites provides an efficient method of sampling large populations of adults.